Optimization of Process Parameters for the Carbonization of Flamboyant Pod Bark (Delonix Regia) - M. O., Aremu,; A. O., Alade,; D. O., Araromi,; A., Bello, (European Scientific Journal, ESJ, 2017)
This study investigates the carbonization of flamboyant pod bark (FPB) for the purpose of production of effective activated carbon from the agricultural residue. Central Composite Design (CCD) under the Response Surface Methodology was employed to combine the selected process parameters [Temperature (300 - 600 0C) and Time (30 - 65 mins)] for the carbonization. FPB were collected within the fields of Ladoke Akintola University of Technology, Ogbomoso, mechanically cracked, crushed, washed with distilled water and sun-dried for seven days before eventually subjecting to carbonization, after which the resultant yields were determined and the statistical analysis was evaluated. The maximum (45.45%) and minimum (11.82%) yields were obtained at Run 1 (3000C/30 mins) and Run 11 (6000C/ 65 mins). The quadratic model equation is given as Yield = 23.27 - 3.48A - 4.38B - 2.81A2 + 0.19B2 + 0.11AB and the R2 value for the model equation is 0.9705 while the adjusted as well as predicted R2 values are 0.9459 and 0.8578, respectively. The numerical optimization by the Design Expert (6.0.8) software suggested minimum yield of 12.89%, (600 0C/ 65 mins) at desirability of 0.941. This research has indicated the suitability of using CCD for the optimization of process parameters for the carbonization of Flamboyant Pod Bark.